Bird Species Diversity in Liwa Botanical Garden, West Lampung - Indah Fitri Sari; Nuning Nurcahyani; M. Kanedi; Tugiyono Tugiyono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
The diversity of bird species can reflect the high biodiversity of an area. it means that birds can be used as a bio-indicator of environmental quality. Determining the quality and level ofenvironmental damage can be seen from the diversity of bird species in the region. Environmental quality will be better if the diversity of bird species in the region is diverse.Birds have an important role in protecting the ecosystem in the Liwa Botanical Garden. The presence of birds in the Liwa Botanical Garden has not been well identified. Therefore thisresearch needs to be done. This research was conducted on 12 October 2019 to 20 October 2019 in the Liwa Botanical Garden, West Lampung. Data collection of bird species isconducted in the morning at 06.30.00-08.30 West Indonesia Time and afternoon at 16.30-18.00 West Indonesia Time, with a combination of the count point and the transect method then all encounters with birds are recorded and identified directly at the study site. After the birds are identified, data is processed to find out Shannon's level index and diversity index. The species diversity index uses the Shannon and Weiner formula. The level of diversity is determined based on the species diversity index. The results showed that there were 15 bird species with a total of 466 individuals with a moderate diversity  index and an evenness index indicating a distressed community.